DAMPAK PROMOSI KESEHATAN TERHADAP PENINGKATAN PERILAKU KUNJUNGAN KE DOKTER GIGI PADA ANAK USIA 6-12 TAHUN: SCOPING REVIEW - Dyah Retnowati (Muhammadiyah University Press, 2022)
Background: Regular visits to the dentist have an impact on dental and oral health. Health promotion about the importance of visiting the dentist, raising awareness in maintaining oral and dental health in elementary school children, thereby improving the behavior of visiting the dentist. This literature review is a type of scoping review that discusses the impact of health promotion in children aged 6-12 years on improving the behavior of visits to the dentist. Objective: To find out how health promotion has an impact on improving the behavior of visits to the dentist in children aged 6-12 years. This scoping review used a search process that refers to statements with the PCC method, namely Population (P), Concept (C), and Context (C). Inclusion Criteria: (1) articles from 2016-2021, (2) children aged 6-12 years, (3) articles discussing changes in the behavior of visits to the dentist, (4) cross-sectional articles, (5) articles using English. Sources of evidence: Databases from: (1) Springer, (2) PubMed, (3) ScienceDirect, (4) SAGEjournal, and (5) Google Scholar. Charting method: Used a PRISMA flow diagram. Result: The health promotion programs used in the four articles are HPS (Health Promoting School), SOHPP (School Oral Health Promotion Programme) and Education. The results of visits to the dentist after being given a health promotion program were found to increase in SOHPP and HPS, while education was found to be no improvement. Conclusion: The HPS and SOHPP health promotion programs created by the government have the effect of increasing visits to dentists in children aged 6-12 years. Factors related to visits to the dentist found can be influenced by the lack of parental time and logistical problems.